The definition of cryptocurrency and mining for the purposes of tax regulation - Tumass, Edgars (Riga Graduate School of Law, 2020)
The work aims to determine the main problems and gaps in cryptocurrency and mining taxation with the aim of proposing an effective hypothetical model of tax regulation for the hypothetical country in which it is absent. Research has shown that 2020 year will be a turning point for cryptocurrencies, and the culmination of this process will be either that they firmly enter the mass circulation, or begin to gradually disappear. In many developed countries, government agencies have actively taken up the collection of taxes from users of the crypto industry, in rarer cases, authorities, on the contrary, try to mitigate the tax burden, and the reasons are: either support for the crypto industry, or simply the lack of deep blockchain monitoring tools. What is more, the main aspects that the state should consider when introducing and working with tax incentives are to improve the introduction of tax incentives to ensure that funds left at the disposal of citizens and enterprises as a result of applying tax incentives contribute to the achievement of state goals and priorities.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Cryptocurrencies